Alkalinization Scenarios in the Mediterranean Sea for Efficient Removal of Atmospheric CO2 and the Mitigation of Ocean Acidification - Butenschön, Momme; Lovato, Tomas; Masina, Simona; Caserini, Stefano; Grosso, Mario (Frontiers in Climate, 2021)
It is now widely recognised that in order to reach the target of limiting global warming below 2 °C above pre-industrial levels (as the objective of the Paris agreement) there is the need for development and implementation of active Carbon Dioxide Removal (CDR) strategies. Relatively few studies have assessed the mitigation capacity of ocean-based Negative Emission Technologies (NET) and the feasibility of their implementation on a larger scale to support efficient implementation strategies of CDR. This study investigates the case of marine alkalinisation, which has the additional potential of contrasting the ongoing acidification resulting from increased uptake of atmospheric CO2 by the seas. More specifically, we present an analysis of ocean alkalinisation applied to the Mediterranean Sea taking into consideration the regional characteristics of the basin. Rather than using idealised spatially homogenous scenarios of alkalinisation as done in previous studies, we use a set of numerical simulations of alkalinisation based on current shipping routes to quantitatively assess the alkalinisation efficiency via a coupled physical-biogeochemical model over the next decades. Simulations suggest the potential of nearly doubling the carbon-dioxide uptake rate of the Mediterranean Sea after 30 years of alkalinisation, and of neutralising the mean surface acidification trend of the baseline scenario without alkalinisation over the same time span. These levels are achieved via two different strategies: a first approach applying constant annual discharge of 200Mt Ca(OH)2 over the alkalinisation period and a second approach with gradually increasing discharge proportional to the surface pH trend of the baseline scenario reaching similar amounts of annual discharge by the end of the alkalinisation period. We demonstrate that via the latter approach it is possible to stabilise the mean surface pH at present day values and substantially increase the potential to counteract acidification relative to the alkalinity added while the carbon uptake efficiency is only marginally reduced. Nevertheless, significant local alterations of the surface pH persist, calling for an investigation of the physiological and ecological implications of the extent of these alterations to the carbonate system in the short to medium term in order to support a safe, sustainable application of this CDR implementation.